2022
DOI: 10.5334/aogh.3711
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Current and Former Teleradiology Systems in Africa: A Review

Abstract: Background: Teleradiology has grown tremendously across the globe, providing significant benefits to both patients and physicians. In the late 1990s, South Africa sought to lead teleradiology adoption efforts by creating a national telemedicine system through a structured and phased approach. Although initial reports of the system's effectiveness were encouraging, the present status of this project, as well as comparable efforts in surrounding developing countries, has remained uncertain.Objective: To explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…There is a paucity of training on the application and benefits of teleradiology for the parties engaged in Kenya, Ghana, and Egypt, [13], [17], [20]. In addition, it was found that none of the countries that had introduced teleradiology had enough in-service training for its medical professionals.…”
Section: Discussion Of Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of training on the application and benefits of teleradiology for the parties engaged in Kenya, Ghana, and Egypt, [13], [17], [20]. In addition, it was found that none of the countries that had introduced teleradiology had enough in-service training for its medical professionals.…”
Section: Discussion Of Objectivesmentioning
confidence: 99%
“…The use of articles from diverse countries makes this paper unique from other publications such as that of Tahir et al, who only focused on Nigeria. Furthermore, this study fills the gap of Ewing & Holmes, who used only six articles from six African countries to make conclusions on the experiences of teleradiology in Africa, [13]. Moreover, these article reviews have not focused holistically on the various teleradiology modalities used by these countries and the successes or failures encountered during the implementation and use of teleradiology in these African countries.…”
Section: Introductionmentioning
confidence: 99%
“…76 The benefits of teleradiology, have been well-described in the literature and teleradiology has been shown to be beneficial for both patients and physicians. 76 A successful teleradiology programme will enable underserved communities to access investigations without the need to travel long distances and is a valuable tool to lessen workforce shortages in Low Middle Income Countries. Data on teleradiology in SSA are sparse but what little are available suggest that it is not yet employed to its full capacity.…”
Section: Measures Underway To Improve Ibd Diagnostic Capacity and Med...mentioning
confidence: 99%
“…Teleradiology is another potential modality to strengthen digital imaging in SSA. 76 The benefits of teleradiology, have been well-described in the literature and teleradiology has been shown to be beneficial for both patients and physicians. 76 A successful teleradiology programme will enable underserved communities to access investigations without the need to travel long distances and is a The need to improve pathology services in SSA has also long been recognized.…”
Section: Histopathology Services In Ssamentioning
confidence: 99%
See 1 more Smart Citation